POLO-ALVARADO, Lorna: Vida de mujeres. Entre la sumisión y la subversión. San Juan, Luscinia, 2018, 157 pp - Salazar Mendoza, Margarita (2019)
https://revistaseug.ugr.es/index.php/arenal/article/view/9217